Towards an MIT-conscious biblical studies in South Africa?: glimpsing the stories of absent husbands and waiting wives - Masenya, Madipoane (Old Testament essays, 2017)
When considering the place of Biblical Studies as a school subject in South African history, one cannot but be reminded of the (predictable) fate of the proverbial eagle. Says one African proverb: o se bone go akalala ga bonong, go wa fase ke ga bona (do not be puzzled by the (pride) of an eagle which soars so high, its fall is certain). Considering the present (slippery) place of (traditional) Biblical Studies as offered in South African institutions of higher learning, the subject's future appears to be gloomy. In the era of the MIT's (Multi-, Inter-,and Transdisciplinarities), biblical scholars should be persuaded to move away from their discipline-specific silos to engage with other disciplines in order for the subject to enrich other disciplines and vice versa. If disciplines such (African) History and Folklore Studies are made to interact with the subject of Biblical Studies, which contribution may such a "merger" bring to biblical scholarship in (South) Africa today? As an attempt to answer the preceding question, this article will use the stories of two waiting women, that is Dora Motshabi (cf. the South African context) and Bathsheba (cf. the monarchic Israelite context) as enablers for the construction of an MIT-conscious Biblical Studies.